The Effectiveness of the Two Stay Two Stray Learning Model Against UPT Student Mathematics Learning Outcomes. SMP Negeri 1 Laut Tador - Anzani, Putri; Maryanti, Indra (EDUCTUM: Journal Research, 2022)
This study aims to find out whether the Two Stay Two Stray learning model is effective for use in learning and to find out whether there is an increase in student learning outcomes by using the Two Stay Two Stray learning model for mathematics learning outcomes of UPT.SMP Negeri 1 Laut Tador Academic Year 2022/ 2023. The population of this study were all students of class VII UPT.SMP Negeri 1 Laut Tador, totaling 130 students. While the sample used in this study was UPT.SMP Negeri 1 Laut Tador class VII-1 students, totaling 26 students. This study uses a type of quantitative research with a research design that is one-group pretest-posttest design. The data analysis technique used in this study is the normality test using the Kolmogorov Smirnov test and hypothesis testing using the t test. the data tested will be processed using the SPSS program. the results of the research that has been carried out show that the value of the g factor ranges from -10.75 (low category) to 49.5 (high category). With the percentage of the g factor which is in the low category which is 26.6% and the percentage of the g factor which is in the high category which is 73.3%. Whereas in the medium category and the false category is 0% and from the data it can be obtained that the average value of the g factor is 9.71%, so it is included in the high-quality category. So, it can be concluded that the use of the Two Stay Two Stray model is effective on student learning outcomes in Mathematics at UPT.SMP Negeri 1 Laut Tador TP. 2022/2023